A Framework for Efficient Information Retrieval Using NLP Techniques - Subhashini, R.; Senthil Kumar, V. Jawahar (Computer Networks and Information Technologies, 2011)
In the academic area, the Internet is used as a scientific resource. However, finding appropriate information on the Web remains difficult. To simplify this process, we designed the Information retrieval framework to retrieve information from the Web Using NLP Techniques. Many information retrieval systems are based on vector space model (VSM) that represents a document as a vector of index terms. To remedy this problem, documents and queries are optimized using NLP. In this paper, the architecture of the proposed tool is presented and it proposes a new approach over the traditional VSM by considering only the nouns and verbs of the documents extracted from NLP as the constituting terms for the VSM instead of the traditional term "word". Such a mechanism may raise the effectiveness of the Information Retrieval by increasing the evaluation metrics values.